Fekete -Szego Problem for Starlike of Complex functions of Order Related to Generalized Derivative Operator (Journal of Humanitarian and Applied Sciences, 2019)
The purpose of the present paper is to investigate the Fekete-Szego problem for certain new subclasses   starlike and convex functions of complex of order  denoted by and  respectively, which involving certain a generalized derivative operator defined in [8]. Various known or new special cases of our results are also pointed out.
Keywords: Analytic functions; Starlike of complex of order; Convex of complex of order; generalized derivative operator